Efficacy of endophytic fungi isolated from Azadirachta indica roots against Alternaria causing early blight of tomato - Ododa, Kennedy Okoth; Githae, Eunice; Muraya, Moses (Jurnal Online Pertanian Tropik, 2023)
Many medicinal plants are reported to host a myriad of beneficial endophytic microbes. Among the well-known medicinal plants is Azadirachta indica (Neem; Family Meliaceae), which has gained worldwide importance due to its extensive array of therapeutic and insecticidal qualities. The use of A. indica extracts in the treatment of plant pathogens has been the subject of extensive investigation, but its endophytic microbes as potential biocontrol agents have received very little attention. In this study, the efficacy of endophytic fungi isolated from A. indica roots against Alternaria, which causes tomato early blight, was examined. Isolation and characterization of Alternaria species and endophytic fungi were done in the laboratory using standard procedures. An in-vitro assay of the endophytic fungi isolates against Alternaria was conducted in a complete randomized design in order to determine the percentage zone of inhibition. The colonies of Alternaria isolates were fast-growing, black to grayish-brown, and suede-like. The conidial length from different isolates was statistically significant (p Ë‚ 0.05) and ranged from 15 Î¼m to 46 Î¼m. The conidial widths were not statistically significant (p > 0.05) and ranged from 8 Î¼m to 15 Î¼m, while the conidial area ranged from 120 Î¼m to 690 Î¼m. A total of seven species of endophytes were isolated from the root of Azadirachta indica: Phoma, Actinomycetes, Chaetomium, Trichoderma, Verticillium, Penicillium, and Fusarium. There was a significant difference in the zones of inhibition (p Ë‚ 0.05), which ranged from 0.0 mm (Actinomycetes) to 3.44 mm (Trichoderma). These isolates could be used to create brand-new organic antifungal substances that are efficient against a variety of plant fungal pathogens.